Atividade antimicrobiana e antibiofilme de óleo de Thymus vulgaris frente à Streptococcus mutans - Rosa, Daniela Dalcin da (2021)
The caries desease is still a major challenge, despite all the means available today for your treatment. The development of caries lesions in the oral cavity is the simultaneous combination of several factors, being considered primordial, the presence of cariogenic microorganisms, the content of the diet and an oral hygiene incapable of efficiently disorganizing the biofilm present on the surface of the teeth. Described as an infectious, multifactorial and transmissible disease, it is considered by the World Health Organization one of the main risk diseases for oral health. Triggered and perpetuated by Gram-positives, where the primary etiologic agent is the bacterium Streptococcus mutans, whose biofilm formation, resistance to conventional antibiotic therapy and oral antiseptics, require the search for new methods to support clinical treatment. In this approach, research that seeks to identify natural products with biological activity represent an alternative for the treatment of this disease. In this context, the use of herbal medicines has been a therapeutic option for health professionals who seek new alternatives with potential pharmacological activity, less toxicity and lower costs to the population. The present work had as objective to evaluate the antimicrobial and antibiofilm activity of the essential oil of Thyme (Thymus vulgaris) against S. mutans. The oil characterization was performed by GC-FID and GC-MS, where it was observed the presence of major components, ο-cymene and thymol in their respective percentages of 47,40% and 27,186%. The antimicrobial activity was evaluated by a conventional broth microdilution method. The T. vulgaris oil was able to inhibit bacterial growth at a minimum inhibitory concentration (MIC) and a minimum bactericidal concentration (CBM) of 0.375mg/mL, in vitro susceptibility tests were performed according to CLSI 2018. The capacity of biofilm formation was evaluated in an ex vivo model, using a bovine teeth model. The antibiofilm activity was analyzed through atomic force microscopy and viable microorganisms counting, demonstrating that the T. vulgaris oil at concentrations of 0.75 mg/mL and 1.5 mg/mL in both techniques promoted a reduction in the formed biofilms.It is hoped that these results can guide future studies for the production of formulations that can be used in the treatment of biofilms caused by S.mutans. Keywords: